Assessment of Anti-Inflammatory and Antioxidant Activities of a Proprietary Preparation of Quercetin–Rutin Blend (SophorOx™) in Exercised Rats - Devanand Shanmugasundaram; James Martin Roza (The Scientific World Journal)
Objectives. Flavonoids comprise a huge class of phenolic compounds widely distributed throughout the plant kingdom. Although quercetin and rutin have been studied individually for their therapeutic value, the synergistic effect of combining the two has previously not been measured. The objective of this trial was to evaluate the anti-inflammatory and antioxidant properties of both quercetin and rutin when combined in the form of SophorOx™ (a proprietary preparation of quercetin–rutin) in exercised rats. Methods. Sprague–Dawley rats were orally administered SophorOx™ at 500 mg·kg−1·b.w. and subjected to daily exercise on a fabricated treadmill for 4 weeks. A total of 24 animals were randomly divided into four groups. All the animals were examined for body weight, feed consumption, signs of clinical abnormalities, and morbidity. In addition, serum collected on days 8, 15, 22, and 29 were measured for the liver function test (LFT), random blood sugar (RBS), inflammatory markers C-reactive protein (CRP), oxidative stress markers (8-isoprostane (8-iso-PGF2α), malondialdehyde (MDA), 8-hydroxydeoxyguanosine (8-OHdG), and cytokine levels interleukin-1β (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor-α (TNF-α)) by the ELISA method. Results. Rats that received SophorOx™ showed no signs of adverse effects, and no significant changes were observed in body weight, feed consumption, liver enzymes, and blood glucose levels. The exercise-treated rats administered with SophorOx™ exhibited a significant reduction in oxidative and inflammatory marker levels, viz., CRP (113.32 ng·mL−1) and oxidative stress markers 8-OHdG (19.32 pg·mL−1), MDA (1.06 nmol·mL−1), 8-iso-PGF2α (1.29 ng·mL−1), IL-1β (0.77 pg·mL−1), and IL-6 (317.14 pg·mL−1) in comparison to those rodents that were exercised without SophorOx™. Conclusion. Oral administration of SophorOx™ significantly reduced oxidative stress and inflammatory marker levels when measured in the rodents subjected to high-intensity exercise.